PERLAKUAN AKUNTANSI AKTIVA TETAP PADA PT. ARINA KARYA SENTOSA NEUSU BANDA ACEH - -, Aliamin (Jurnal Akuntansi Muhammadiyah, 2010)
The aim of this research was to know how the fix assets record in PT. Arina Karya Sentosa (subject of research), what is the assets recorded as of Indonesian Accounting Standard (Standar Akuntansi Keuangan/SAK).The method to use of this research was qualitative descriptive, the operating of this method are  to compare both the theoretical with  PT Arina Karya Sentosa recorded to fix assets, and recently the researcher make decisions and recommendation to improve the fix assets recording system.The result of this research were to find PT. Arina Karya Sentosa Banda Aceh classified fix assets to; buildings, project equipments, office equipments, vehicles. The depreciation method to measure the right value of all assets was manual method that they use to measure their assets, did not use method recommendation from Indonesian Accounting Standard.Even thought, PT. Arina Karya Sentosa was recording and prepare the  fix assets as of Indonesian Financial Accounting Standard in financial report, except the depreciation method but in audit review by independent auditor these was no problem. Key words:  fix assets recording, fix assets method, fix asset prepare in financial report.